Окремі проблемні аспекти правового статусу неповнолітніх як суб'єктів правовідносин - Котюк, І.І.; Пасєка, М.О. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Раскрываются проблемные аспекты правового статуса несовершеннолетних. Обращается внимание на несовершенство понятийно-категориальных подходов законодательства Украины в отношении несовершеннолетних. Подчеркивается необходимость усиления государственно-правового внимания к их проблемам и прежде всего совершенствования регламентации их правового статуса, определения их прав и свобод, а также создания эффективных механизмов их обеспечения, путем приведения их в соответствие с международными стандартами в этой сфере. Based on analysis of existing legislation are being problematic aspects of the legal status of minors. Attention is drawn to the inadequacy of concepts and categorical approaches of Ukrainian legislation with regard to minors. Emphasizes the need for greater public attention to their legal problems and, above all, to improve the regulation of their legal status, define their rights and freedoms, as well as the establishment of effective mechanisms for their security,by bringing them into line with international standards in this area.